Pelatihan Pemasaran Melalui Media Sosial Sebagai Upaya Menyiapkan Kompetisi Pasar: Pengabdian - Lusi Andriyani; Siska Yuningsih; Sri Yunanto; Usni; R. Hiru Muhammad; Donny Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Kuripan Village, Ciseeng District, Bogor Regency, have significant potential in the local food sector, but face serious marketing challenges, particularly limited digital literacy. This condition makes their products less competitive in the modern market. This community service activity aims to increase the competitiveness of MSMEs by optimizing marketing based on social media and digital platforms. The implementation method is online training via Zoom with an interactive, participatory, and applied approach, covering three main topics: social media ethics, basic product photography techniques, and creating online business accounts. The activity participated in 10 local MSMEs. The evaluation results showed a significant increase in participants' understanding and skills, marked by an average pretest/posttest score that increased from 2.4 to 4.5 in the ethics aspect, from 2.1 to 4.2 in videography skills, and from 1.8 to 4.6 in mastery of digital business accounts. Participant testimonials also indicate a change in mindset and courage to utilize digital media as a promotional tool. Thus, this activity effectively bridges the digital divide of local MSMEs and contributes to strengthening technology-based marketing capacity.